PENGARUH ROA, NIM, NPL, DAN EPS TERHADAP HARGA SAHAM PERBANKAN BUMN (2016-2023) - Sari, Permata; Priharta, Andry; Riyanti, Riyanti (Media Riset Bisnis Ekonomi Sains dan Terapan, 2025)
This study investigates the influence of Return on Assets (ROA), Net Interest Margin (NIM), Non-Performing Loan (NPL), and Earnings per Share (EPS) on the stock prices of state-owned banks (BUMN) in Indonesia during the 2016–2023 period. The research applies a quantitative associative approach using saturated sampling, with the population consisting of annual financial reports from PT Bank Mandiri (Persero) Tbk, PT Bank Rakyat Indonesia (Persero) Tbk, PT Bank Negara Indonesia (Persero) Tbk, and PT Bank Tabungan Negara (Persero) Tbk. The sample comprises eight years of data collected from 2016 to 2023. Data were analyzed through multiple linear regression using EViews. The results reveal that NIM, NPL, and EPS significantly affect stock prices, while ROA shows no significant effect. These findings highlight that profitability measured by ROA is not a determining factor in stock price movements of state-owned banks, whereas NIM, NPL, and EPS play a more critical role in influencing investor decisions and market valuation. Keywords : Earnings per Share (EPS), Net Interest Margin (NIM), Non-Performing Loan (NPL), Return on Assets (ROA), Stock Price.